Titanium dioxide nanotubes as reinforcement of a selfadhesive resin cement in self-curing mode - Pacheco, Leandro Edgar (2019)
Objective: This study has analyzed bond strength to root dentine and to fiberglass posts, and the radiopacity of self-adhesive dual resin cement in addition of titanium dioxide nanotubes (nt-TiO2) in self-curing polymerization. Material and Methods: The self-adhesive resin cement (RelyX U200TM, 3M ESPE) was enhanced with different concentrations (0.3, 0.6, and 0.9% by weight) of nt-TiO2 and evaluated at only self-curing mode. To test the bond strength to root dentine and fiberglass posts was applied the push out bond strength test (PO). To analyze the radiopacity was follow the ISO standard (9917-2/2010). Data were statistically analyzed by one-way ANOVA test, followed by post hoc multiple comparisons Fishers test for PO and Tukeys test for RO (p<0.05). Results: Reinforced self-adhesive resin cement influenced the increase in values of PO, especially in the S06 group (0.6 wt%), which demonstrated a higher value of bond strength, mainly in the apical third. However, this analysis not demonstrated statistical difference between the groups with nt-TiO2 addition (S03, S06 and S09) and the control group (SCT). For radiopacity, the addition of nt-TiO2 may provide an increase in value, especially to the S09 group, which showed a higher value with statistical difference in comparison with SCT group. Conclusion: The addition of nt- TiO2 showed influence at behavior of the self-cure mode of the self-adhesive resin cement, and its use in other concentrations may be considered for future studies, since reinforced cement may prove better results in indirect restorative procedures.